2019
DOI: 10.1016/j.compositesb.2019.107191
|View full text |Cite
|
Sign up to set email alerts
|

Low velocity impact behavior of interlayer hybrid composite laminates with carbon/glass/basalt fibres

Abstract: This work investigates the effects of carbon/glass/basalt hybridization and fabric structure on the low velocity impact resistance of fibre reinforced plastic composites. Interply hybrid specimens used in the study were fabricated in a sandwich-like stacking sequence using a vacuum assisted resin infusion molding technique. Low velocity impact tests were carried out to study effects of hybridization and fabric structure on the impact resistance of composite laminates. A continuum damage mechanical model was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(57 citation statements)
references
References 55 publications
2
55
0
Order By: Relevance
“…On the other hand, delamination developed in samples with a/t = 0.5 was observed to begin from the edge of the initial surface crack. This suggests that the stress intensity of the initiation cracks is severe enough to trigger delamination between laminates [28].…”
Section: Damage Progression By Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, delamination developed in samples with a/t = 0.5 was observed to begin from the edge of the initial surface crack. This suggests that the stress intensity of the initiation cracks is severe enough to trigger delamination between laminates [28].…”
Section: Damage Progression By Impactmentioning
confidence: 99%
“…The formation and progression of surface cracks are also very important in composite materials [1,24,25]. For this reason, materials are expected to exhibit the mechanical behavior predicted in the design and keep the structural integrity under impact loads [26][27][28]. The chemical and mechanical effects on the surface of materials may result in notches or cracks [29].…”
Section: Introductionmentioning
confidence: 99%
“…Among the typical damage modes for composites, delamination is regarded as the most significant mode because it may propagate undetectably and result in the unforeseen collapse of the structures [35]. The cohesive zone model (CZM) has been widely used in many previous works [36,37,38,39,40,41]. The mixed mode cohesive laws have to reduce to the corresponding normal and tangential tractionseparation laws under pure mode loading.…”
Section: Introductionmentioning
confidence: 99%
“…The study highlights the importance of predictive models (e.g., FEA) for the purpose of estimating the behaviour of printed composites and optimizing their mechanical properties. Numerical analyses show that in the case of impact tests, they are close to experimental measurements [ 34 ]. Implemented impact tests have shown that the thickness of the lamina, the volume fraction of the fibre and the build orientation have an effect on the amount of absorbed energy.…”
Section: Introductionmentioning
confidence: 75%